Zinc in fibromyalgia patients: relationship with body mass index and sleep quality - Ece, Yiğit (Publishing Office of the University of Rzeszow, 2022)
Introduction and aim. Given the potential relationship between oxidative stress and fibromyalgia and well-documented antioxidant efficacy of zinc, the present study aimed to determine serum zinc concentration in FM patients as compared to healthy controls, as well as to identify the correlation of serum zinc concentration with the body mass index (BMI) and sleep quality, Material and methods. In this case-control study, 54 fibromyalgia patients were consecutively recruited between October 01, 2021 and December 01, 2021. The control group consisted of 54 age- and sex-matched healthy controls. Results. Fibromyalgia group had significantly lower zinc concentration, higher body mass index, and lower sleep quality scores as compared to the healthy control group. The correlation analysis revealed a significantly negative correlation between serum zinc concentration and body mass index and a significantly positive correlation between serum zinc concentration and sleep quality both in fibromyalgia and healthy control groups. Conclusion. Our results both support the hypothesis that low serum zinc concentration plays a role in the pathophysiology of fibromyalgia and indicate that fibromyalgia may lead to weight gain and poor sleep quality, which needs to be confirmed in large-cohort studies.
The study was approved by the Non-Interventional Clinical Research Ethics Committee of Istanbul Medipol University (Date 14/10/2021, Decision No:1009).
Keywords: body mass index; fibromyalgia; sleep quality; zinc